Latvijas reģionu tautsaimniecības attīstība - Boreiko, Karīna (Latvijas Universitāte, 2012)
Bakalaura darba tēma ir Latvijas reģionu tautsaimniecības attīstība. Darba mērķis ir noskaidrot un analizēt galvenos Latvijas reģionu attīstību raksturojošos rādītājus, parādīt katra reģiona tautsaimniecības attīstības līmeni, kā arī izteikt priekšlikumus situācijas uzlabošanai. Bakalaura darba teorētiskā un analītiskā daļa ir balstīta uz: LU rakstiem, zinātnisko konferenču tēzēm, Baltic Journal of Economics, Unemployed in Europe, Finance and development u.c. zinātniskajiem žurnāliem, LR likumiem, LR Centrālās statistikas pārvaldes datiem, Nodarbinātības valsts aģentūras datiem, EUROSTAT datiem, un citiem speciālās zinātniskās literatūras avotiem, uz autores veiktajiem aprēķiniem. Atslēgvārdi: Latvijas reģioni, tautsaimniecības attīstība, demogrāfiskie rādītāji, sociālekonomiskie rādītāji.

The theme of bachelor work is ’Economical development of Latvian regions’. The aim of the work is not only to determine and analyze the main indicators that describe the development of Latvian regions, but also to show the level of economics development for each region and to make suggestions for improvement of economics situation. The practical and theoretical parts are based on LU articles, thesis of scientific conferences, Baltic Journal of Economics, Unemployed in Europe, Finance and development etc. scientific journals, the laws of the Republic of Latvia, the data of Central Statistical Bureau of Latvia, data of State Employment Agency, and other sources of scientific literature, as well on the calculations of author. Keywords – Regions in Latvia, development of country, demographical indicators, social economical indicators.
Economical developmont of regions in Latvia
Keywords: Vadībzinātne